Agroforestry for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Steppler, H A and P K R Nair (eds). 1987. Agroforestry a Decade of Development. ICRAF. Nairobi. 335 pp. ISBN 92-9059-036X